Risk factors for fibroadenoma mammae (FAM) among adult women at the South Tangerang General Hospital in Indonesia - Jaksa, Suherman; Fachri, Muhammad; Andriyani, Andriyani; Lusida, Nurmalia; Ahmad, Gofur; Labib, Muhammad (Trends in Immunotherapy, 2024)
A frequent benign breast tumor, fibroadenoma mammae (FAM), has extra stromal and epithelial components in the breast tissue. Despite not being fatal, FAM increases breast cancer risk, highlighting the necessity to recognize it. Estrogen and progesterone levels during menstruation, pregnancy, and lactation may alter FAM development. Therefore, this study examines FAM risk variables in adult women at South Tangerang Regional General Hospital, Indonesia. Adult women in General Hospital of South Tangerang City, Indonesia were studied using a case-control design with 85 cases and 85 controls. South Tangerang General Hospital recruited volunteers between December 2023 and January 2024 using purposeful sampling. FAM patients with a history of therapy were cases, while Eye Clinic patients without FAM were controls. Viral diseases, major cardiovascular problems in the past three years, and unstable weight were excluded. Multivariate analyses employed multiple logistic regression, while univariate and bivariate analyses used percentages and chi-square test. Fibroadenoma mammae (FAM) prevalence in adult women at South Tangerang General Hospital is highly correlated with age, age of menarche, family history, hormonal contraceptive use, and nutritional status. Abnormal nutrition was the largest risk factor for FAM in hospitalized adult women (aOR = 8.678, p < 0.000). The study stresses the link between nutritional state and FAM, with abnormal nutritional status increasing risk. This shows how diet and nutrition affect FAM sensitivity. To reduce FAM prevalence, demographic, genetic, hormonal, and lifestyle factors must be understood and addressed due to their complex interaction. Dietary strategies that promote healthy eating may reduce FAM risk.